DAMPAK PROGRAM CENTRE OF EXCELLENCE (COE) BINA KELUARGA LANSIA (BKL) DALAM MENINGKATKAN KUALITAS HIDUP LANSIA - Desy Tariustanti; Zarah Puspita; Al Munawir (LPPM STIKES Muhammadiyah Kendal, 2023)
Indonesia has doubled the number of elderly people, by 9.92 percent by 2020, or about 26 million people. At this age, older people tend to decline in their physical, psychological, environmental and social functions. The decline in these functions will have an impact on the quality of life of the elderly. Elderly Family Development (BKL) is one of BKKBN's programs that aims to improve knowledge, attitudes and skills that can improve the quality of life of older people. BKL is a place where older people can lead active, productive, healthy and independent lives through the activities of the BKL Group. This study is a methodological study combined with quantitative and qualitative descriptive approaches carried out in the BKL group, at Mimbaan Village, Situbondo Regency. The study was conducted from February to March 2021. Informants included in this study included key informants, additional informants, and key informants. The main informants are the elderly of the CFSC, the providers of additional information are the village midwives or nurses, the agricultural extension agents of the CFSC and the staff of the CFBs. The main informant was the head of the National Population and Family Disasters Authority Situbondo Regency. The results show that the Elderly Family Development Program has a positive impact on the lives of the elderly and can improve the quality of life of the elderly. The results of interviews with all informants indicate that the activities carried out in the NCD program affect the physical, psychological, social and environmental aspects, thus they have an impact on quality improvement. the life of the elderly. Physical, psychological, social and environmental conditions are factors affecting the quality of life of older people. The existence of the BKL CoE program has a positive impact on the elderly and contributes to improving the quality of life of the elderly.